Feeding ecology of the glacier lanternfish Benthosema glaciale (Actinopterygii, Myctophidae) in the Flemish Cap (North Atlantic Ocean) - García Seoane, Eva; Dalpadado, P.; Vázquez Rodríguez, Antonio (Hydrobiologia, 2013)
14 páginas, 8 figuras, 1 tabla The feeding dynamics of the glacier lanternfish Benthosema glaciale were studied during the summer of 2010 in the Flemish Cap. B. glaciale constituted a majority of the deep scattering layer (DSL), which was located between 300 and 650 m during daylight hours; at night, a part of the DSL migrated to the surface. B. glaciale is a zooplanktivore, feeding primarily on copepods (Calanus hyperboreus, Pareuchaeta norvegica, Metridia longa and Calanus finmarchicus), followed by amphipods (Themisto compressa) and krill (primarily Nematoscelis spp.). Although crustaceans dominated the diet, other invertebrates, such as chaetognaths, gastropods, polychaetes, ostracods and appendicularians, also contributed. The geographical differences in the composition of the diet resulted from the association of prey with distinct water masses. In the colder water at the north of the bank, Arctic species represented a higher proportion of the diet, but this situation was reversed in areas influenced by the warmer water from the south. B. glaciale fed more intensively towards the centre of the Flemish Cap. The diet of B. glaciale shifted ontogenetically, showing increasing prey size and prey diversity with increasing predator size This study was made possible by a JAE Predoctoral Fellowship of the Consejo Superior de Investigaciones Cientificas (CSIC), co-financed by the European Social Fund Peer reviewed